Perspectives of pregnant women, family members and health professionals on medication adherence in Nigeria. Issue 10 (2nd October 2020) - Omonaiye, Olumuyiwa; Nicholson, Pat; Kusljic, Snezana; Manias, Elizabeth
ABSTRACT : Nigeria has the highest burden of mother-to-child transmission of human immunodeficiency virus (HIV) worldwide. Pregnant women living with HIV in Nigeria face challenges adhering to antiretroviral therapy (ART). We explored the perspectives of pregnant women living with HIV, family members, friends and health professionals to understand adherence to ART. Pregnant women, family members, friends and health professionals recruited from four HIV treatment sites in Nigeria participated in semi-structured interviews and focus groups. Thematic analysis was conducted and themes and sub-themes were mapped against the Theory of Planned Behaviour comprising behavioural, normative and control beliefs. Overall, 74 participants took part in the study. Common behavioural beliefs comprised maintaining the mother's and unborn child's health and success of having HIV-negative children from previous pregnancies. Common normative beliefs involved partner and family support for medication taking and medication refill visits. Common control beliefs comprised fear of discrimination and stigmatisation. Results showed that adherence to ART in pregnancy is intricate. Hence, before interventions are developed to change adherence behaviours in pregnant women tailored strategies should be devised that address the salient beliefs that influence adherence during pregnancy.